Rapid preparation of functional polysaccharides from Pyropia yezoensis by microwave-assistant rapid enzyme digest system. (20th November 2016) - Lee, Ji-Hyeok; Kim, Hyung-Ho; Ko, Ju-Young; Jang, Jun-Ho; Kim, Gwang-Hoon; Lee, Jung-Suck; Nah, Jae-Woon; Jeon, You-Jin
Highlights: Pyropia yezoensis is rich in functional sulfated polysaccharides. Harmful acids were used in the typical polysaccharide extraction or isolation. Microwave-assistant enzyme digest system helps a rapid isolation of the polysaccharides. The isolated polysaccharide has strong antioxidant effect. Abstract: This study describes a simple preparation of functional polysaccharides from Pyropia yezoensis using a microwave-assistant rapid enzyme digest system (MAREDS) with various carbohydrases, and evaluates their antioxidative effects. Polysaccharide hydrolysates were prepared using MAREDS under different hydrolytic conditions of the carbohydrases and microwave powers. Polysaccharides less than 10 kDa (Low molecular weight polysaccharides, LMWP, ≤10 kDa) were efficiently obtained using an ultrafiltration (molecular weight cut–off of 10 kDa). MAREDS increases AMG activation via an increased degree of hydrolysis; the best AMG hydrolysate was prepared using a 10:1 ratio of substrate to enzyme for 2 h in MAREDS with 400 W. LMWP consisted of galactose (27.3%), glucose (64.5%), and mannose (8.3%) from the AMG hydrolysate had stronger antioxidant effects than the high molecular weight polysaccharides (>10 kDa). We rapidly prepared functional LMWPs by using MAREDS with carbohydrases, and suggest that LMWP might be potentially a valuable algal polysaccharide antioxidant.